2017
DOI: 10.1080/15569527.2017.1365883
|View full text |Cite
|
Sign up to set email alerts
|

The percutaneous absorption of soman in a damaged skin porcine model and the evaluation of WoundStat™ as a topical decontaminant

Abstract: The current study has shown that the use of WoundStat™ as a decontaminant on damaged pig ear skin was unable to fully protect against GD toxicity. Importantly, the findings indicate that the use of WoundStat™ in GD contaminated wounds would not exacerbate GD toxicity. These data suggest that absorbent haemostatic products may offer some limited functionality as wound decontaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Similarly, Chilcott et al, 2001, showed that the absorption of Sulfur mustard through pig ear skin was 2.6 times higher than that of human skin using 50% aqueous ethanol in the receptor medium. Finally, other studies showed that using another receptor medium, such as ethanol and water (1:1) (Dalton et al, 2018;Thors et al,2016) or HBSS solution (Bignon et al, 2017), does not impact the penetration of compounds through the skin. The use of different membranes origins at the interface of the diffusion device can lead to differences in the evaluation in skin decontaminants (Chilcott et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chilcott et al, 2001, showed that the absorption of Sulfur mustard through pig ear skin was 2.6 times higher than that of human skin using 50% aqueous ethanol in the receptor medium. Finally, other studies showed that using another receptor medium, such as ethanol and water (1:1) (Dalton et al, 2018;Thors et al,2016) or HBSS solution (Bignon et al, 2017), does not impact the penetration of compounds through the skin. The use of different membranes origins at the interface of the diffusion device can lead to differences in the evaluation in skin decontaminants (Chilcott et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of extremely toxic compounds such as Organophosphorus Nerve Agents, trauma casualties may be at high risk of death. The issue of wound contamination and decontamination is thus very theoretical [ 18 , 19 ].…”
Section: Other Considerationsmentioning
confidence: 99%
“…However, this practice is not supported as the tolerable concentration of bleach is generally insufficient for the timely neutralisation of chemical contaminants and may itself result in toxicity. Current evidence suggests that powder-based, absorptive haemostatic products are effective skin and wound decontamination products for chemical warfare agents [ 18 , 19 ], although the specialist nature of such products would likely preclude their availability at the scene of a civilian CBRN incident. Some recent studies have shown that products like Woundstat might be interesting, but the protocol used is not directly applicable to field situations except when wound contamination takes place while managing a casualty and when action can be taken immediately.…”
Section: Other Considerationsmentioning
confidence: 99%
“…In certain cases, there is the potential to inadvertently produce toxic breakdown products, as observed with the degradation of VX (Munro, 1999). A wide range of products have been evaluated for decontamination of surfaces (Capoun, 2014;Yang, 1992); however, few of these are suitable for skin decontamination (Salerno, 2016;Schwartz, 2012;Thors, 2017), especially if the skin is damaged (Dalton, 2017;Lydon, 2017). Given the lack of medical treatments for some chemical contami nants, such as sulphur mustard, decontamination can be used to mitigate toxic effects by reducing the contaminant and…”
Section: Introductionmentioning
confidence: 99%